2012
DOI: 10.2478/s11536-012-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Effective melatonin protection of burn-induced hepatic disorders in rats

Abstract: AbstractWe studied the effect of melatonin on morphological and functional disorders using serum markers of liver dysfunction such as cholinesterase and gamma glutamyl transpeptidase, hepatic protein content and malondialdehyde in a burned-rat model. Melatonin (10 mg/kg (−1), i.p) was administered immediately and then 12 h after 30% of total body surface area burns of male Wistar rats. The burns induced an increase of hepatic malondialdehyde levels by 166% (p<0.001), and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Melatonin exhibited various biological activities, such as antioxidant and anti-inflammatory effects, and has been reported to display significant beneficial effects against burn-induced cellular injury [ 96 ]. In a burned-rat model, enhancement in hepatic MDA level ( p < 0.001), vascular congestion, leukocyte infiltration around the central veins, intracellular vacuolization, hepatic cell degeneration, and apoptotic bodies were observed [ 97 ]. Moreover, elevated hepatic MDA was reduced ( p < 0.01), and degenerative changes in the hepatocytes were restricted by administration of melatonin [ 97 ].…”
Section: Protective Effects Of Melatonin On Liver Injuriesmentioning
confidence: 99%
“…Melatonin exhibited various biological activities, such as antioxidant and anti-inflammatory effects, and has been reported to display significant beneficial effects against burn-induced cellular injury [ 96 ]. In a burned-rat model, enhancement in hepatic MDA level ( p < 0.001), vascular congestion, leukocyte infiltration around the central veins, intracellular vacuolization, hepatic cell degeneration, and apoptotic bodies were observed [ 97 ]. Moreover, elevated hepatic MDA was reduced ( p < 0.01), and degenerative changes in the hepatocytes were restricted by administration of melatonin [ 97 ].…”
Section: Protective Effects Of Melatonin On Liver Injuriesmentioning
confidence: 99%
“…Among these studies, the sample size per group ranged from 3 to 19. Eight studies focused on hepatic injury [63][64][65][66][67][68][69][70], four on gastric mucosal damage [45,[71][72][73], two on kidney injury [74,75], two on plasma [76,77], one on intestine injury [78], and one on lung injury [79]. All of the studies used hot water (90-100 • C) to induce burn wounds in rats.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, allocation concealment and random outcome assessment were not described, resulting in a high risk of selection and detection bias, respectively, in all studies. In addition, the issue of selective reporting was not discussed in two studies [64,68], suggesting that they may have had a high level of reporting bias. All of the studies reported that the animals were of similar weight and underwent the same experimental design at baseline.…”
Section: Risk Of Bias and Quality Of Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to that evidence, application of melatonin would be suitable for relief from those diseases and can be designated as a drug for supportive care [72]. The supportive role of melatonin in burn therapy [73,74] and inflammatory bowel disease [75] are two examples.…”
Section: Effect On Immune System Stimulus Organism Referencementioning
confidence: 99%